Metrology in Chemistry - Bulska, Ewa.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
In this concise book, the author presents the essentials every chemist needs to know about how to obtain reliable measurement results. Starting with the basics of metrology and the metrological infrastructure, all relevant topics - such as traceability, calibration, chemical reference materials, validation and uncertainty - are covered. In addition, key aspects of laboratory management, including quality management, inter-laboratory comparisons, proficiency testing, and accreditation, are addressed. .
Introduction -- General aspect of metrology -- Metrological infrastructure -- System of units -- Metrological traceabilityTesting and calibration -- Chemical reference materials -- Validation of the measurement procedure -- Uncertainty of results -- Quality management -- Inter-laboratory Comparisons (ILC)/Proficiency Testing (PT) -- Accreditation of chemical laboratories -- Basic operation on numbers.
Keywords: Analytical chemistry; Measurement; Measuring instruments; Environmental monitoring; Analytical Chemistry; Measurement Science and Instrumentation; Environmental Monitoring